Effective of incentive system on development of Research creativity for professors of university: Analytical study at private collage in Baghdad (Journal of Accounting and Financial Studies ( JAFS ), 2018)
This research aims at studying and analyzing the creative research thinking of the educational staffs in private universities and colleges, and also the role of incentives, in its materialistic and moral sides in the development of such thinking and the pack of restraints which cause decline in interest level of the scientificresearch, and its weak role in the development of universities in Iraq, despite the interest of the Ministry of Higher Education and Scientific Research in Iraq in scientific research as part ofits academic and humanitarian targets.Based on study and analysis, and the using if some of statistical methods such as the Alpha Chronobaghcoefficient and the (T. Test)(F. Test),the research reached a number of conclusions. The most important among these conclusions was the powerful correlative relation between incentives system used in academic institution and the development of research creativeness, in addition to the obvious effect of the incentives system in the development of such creativity.The study offered a set of recommendations, including the necessity ofimproving incentives system in general, and the moral incentives system in special inside academic institutions, provided that the Ministry of Higher Education and Scientific Research in Iraq should adhere to such improvements